Principles and strategies to balance ethical, social and environmental concerns with corporate requirements - Leonard, Liam; Gonzalez-Perez, Maria Alejandra (Advances in sustainability and environmental justice, 2013)
Advances in Sustainability & Environmental Justice Volume 12: Principles and Strategies to Balance Ethical Social and Environmental Concerns with Corporate Requirements brings together a range of practitioners and academics from the world of business who examine corporate social responsibility in policy and practice in a series of case studies from across the globe. This volume, co-edited by Dr. Liam Leonard and Dr. Maria Alejandra Gonzalez-Perez, is the second in the series (formerly Advances in Ecopolitics) dedicated to Corporate Social Responsibility within the scope of international business. Both books in this pair of studies bring together contributions from authors located in 13 countries in the 5 continents, and this second volume on the topic specifically incorporates academic works from 21 researchers representing institutions from Australia, Canada, Colombia, England, Ireland, Kenya, Malaysia, Nigeria, Romania, and the United States. As such, these studies represent one of the most comprehensive collections on contemporary business practices in the significant area of Corporate Social Responsibility.